Bacteroides xylanisolvens possesses a potent anti-hyperuricemia effect in goslings fed on a high-protein diet - Song, Ning; Wang, Mingze; Zhong, Guangxu; Zhu, Kunpeng; Chen, Pengju; Zhang, Naisheng; Liu, Xiaobo; Zhang, Wenlong (Frontiers in Microbiology, 2023)
Hyperuricemia is widespread in humans and birds which is a necessary physiological factor leading to gout. Studies have shown an inextricable relationship between gut microbiota and hyperuricemia. This study explored the association between intestinal flora and hyperuricemia in goslings. The hyperuricemia model was established in gosling by a high protein diet (HPD). 16S sequencing showed that the cecal microbiota differed significantly between the HPD and control groups (fed with the normal protein). The abundance of Firmicutes was higher in the HPD group, while the Bacteroidetes were lower than in controls. To investigate the role of intestinal flora in hyperuricemia, the cecum microbiotas from the HPD group and the control group were transplanted to the newly born goslings by gavage. The serum uric acid levels of the goslings that transplanted the cecal microbiota of the HPD group were significantly higher than the goslings that transplanted the cecal microbiota of the controls. Furthermore, the transplantation of cecal microbiota also affects the production and excretion of uric acid in goslings. Then we identify the gut bacterium Bacteroides xylanisolvens as an effective anti-hyperuricemia in the goslings. B. xylanisolvens reduces serum uric acid concentrations in hyperuricemia in goslings’ model, and it can up-regulation ABCG2 mRNA expression in the kidney, and down-regulation XDH mRNA expression in the liver. These results suggest a possible route to therapy for hyperuricemia and gout in goslings by Bacteroides xylanisolvens.